Reported language attitudes among Norwegian speaking in-migrants in Tromsø - Sætermo, Monica; Sollid, Hilde (Acta Borealia, 2021)
Today, in an era of increased mobility and migration, there is also increased in-migration within regions and countries. In the case of Norway, there is high tolerance for dialect use, and in this context, it is interesting to ask which kinds of sociolinguistic strategies in-migrants consider to be available given their current situation. This article explores the reported language attitudes from the point of view of people who have moved to Tromsø from other parts of Norway. The data is from a survey about (1) in-migrants’ attitudes towards various forms of dialect use, including dialect maintenance, shifts or changes, and (2) how the in-migrants perceive attitudes in Tromsø towards various forms of dialect use. The study shows that it is seen as ideal to maintain one’s initial dialect, rather than changing or shifting the dialect. However, most of the respondents reportedly changed their own initial dialect and changing or shifting the dialect is perceived as a tolerable sociolinguistic strategy to fit in and accommodate the new place. We also find that a common assumption is that people in Tromsø have positive attitudes towards other dialects, but it seems to matter where one comes from and which dialect one speaks.